Genetic and serologic characterization of human herpesvirus type 8 (HHV -8) IN South Africa. - Alagiozoglou, Pandeli (Lee) (My University, 2014)
Human herpes virus type 8 (HHV-8) is strongly implicated as the etiological agent of Kaposi’s sarcoma (KS). The incidence of KS in South Africa is increasing in parallel with the HIV-1 epidemic. Molecular and serological prevalence of HHV-8 in HIV-1 infected individuals with and without KS was investigated. DNA fragments from ORF26 (capsid, 330BAM233) and ORF75 (tegument) regions were used to determine the prevalence of HHV-8 DNA in peripheral blood mononuclear cells (PBMC) from 429 HIV-1 infected individuals, 95 of whom had histologically confirmed KS. Of those without KS, 14 (4.2%) were PGR positive for HHV-8 DNA. In the individuals with KS, the proportion of HHV-8 DNA positive PBMC samples was 11 times higher (46/95,48%). Similarly, an immunofluorescence assay showed that 78% of KS patients had antibodies to HHV-8 compared to 16% of KS negative individuals. Among the KS group, 93% of PCRpositive samples were also HHV-8 antibody positive compared to only 66% of PCR negative samples indicating that viremia is associated with good antibody responses. Matched lymph node and PBMC samples were available for 8 patients. HHV-8 DNA was more frequently detected in the lymph node (3/8) than in the blood (1/8), suggesting that the lymph nodes are a reser / o r for HHV-8. These data confirm the association between HHV-8 and KS and suggest that there is a high background prevalence of HHV-8 infection in HIV-1 infected individuals in South Africa. The ORP 75 gene of 40 HHV-8 strains was sequenced and the phylogenetic relationships between South African and already published sequences were investigated. The majority (n=29) of strains overlapped with the published A and B subgroups and were termed A/B variants.Three strains were classified as subgroup C while 8 sequences did not cluster with any of the previously classified subgroups and were termed novel (N) group. The DNA distance of this novel group differed from the A, B and C subgroups by 4.7%, 3.8% and 4,5% respectively although within the N group there was only 0.4% variation. The addition of this group significantly increased the number of subgroup-specific polymorphisms from 17 to 47 over a 804 bp region. There was sufficient inter-subgroup genetic diversity that single strand conformational polymorphisms (SSCP) could be used to rapidly identify them. Thus, based on the analysis of the ORF75 gene, a unique HHV-8 sub-group is present in South Africa which accounts for 20% of circulating strains. Further studies are required to determine the extent of evolutionary phytogeny, distribution and pathogenic potential of this novel group.
Keywords: Herpesvirus, Kaposi Sarcoma-Associated